Unchanged Erythrocyte Profile After Exposure to Cryogenic Temperatures in Elder Marathon Runners - Szymura, Jadwiga; Wiecek, Magdalena; Maciejczyk, Marcin; Gradek, Joanna; Kantorowicz, Malgorzata; Szygula, Zbigniew (Frontiers in Physiology, 2018)
Objective Endurance runners may experience 'sports anemia' resulting from intravascular hemolysis. In addition, aging has negative impact on hematopoiesis and rheological properties of blood, and erythrocyte membranes in older people are more vulnerable to oxidative damage, which together can lead to anemia. Whole-body cryostimulation (WBCST) is increasingly used in the elderly as a method of biological regeneration of athletes or therapy and preventive treatment. That is why the aim of the study was to determine whether repeated WBCST had an effect on the erythrocyte system in master marathon runners, compared to non-training men. Methods Ten marathon runners (men aged 55.9±5.5 y, training experience 6.71±5.79 y) and 10 non-training (men aged 62.0±5.8 y) were subjected to a series of 24 WBCST (3 min, -130°C) performed every other day. Erythrocyte levels, Interleukin-3, erythropoietin (EPO), haptoglobin, bilirubin and extracellular hemoglobin (HGBecf) concentrations were determined in the blood before and after 12, 24 WBCST, as well as 7 days after their completion. Results The concentrations of EPO and Interleukin-3 were significantly increased 7 days after the completion of WBCST in both groups (P<0.05). The erythrocyte content and indicators, the bilirubin, haptoglobin and HGBecf levels in each group did not change as a result of WBCST. In order to document haemolytic changes and/or factors affecting the severity of erythropoiesis, correlations between growth erythropoietic factors, erythrocyte and haemolytic factors as well as mutual correlations between hemolytic indexes were calculated. There was a positive correlation (P<0.05) between the EPO and Interleukin-3, bilirubin, mean corpuscular hemoglobin and red blood cell distribution width – standard deviation. There was also a positive correlation between the concentrations of bilirubin and HGBecf, and a negative correlation between haptoglobin and HGBecf as well as bilirubin concentrations. Conclusions Whole-body cryostimulation treatments, repeated every other day, do not cause haemolytic changes in elder men with high or low physical activity. But also, they are a procedure that does not increase the level of erythrocytes or their hemoglobinization. In athletes, it is not a form of doping. The positive correlation between EPO and bilirubin may be indicative of, for example, the mutual antioixidative effect of these